A Delphi study on National PICU nursing research priorities in Australia and New Zealand - Ramelet, Anne-Sylvie; Gill, Fenella (Elsevier Inc, 2012)
Background: There is a lack of evidence to direct and support nursing practice in the specialty of paediatric intensive care (PIC). The development of national PIC nursing research priorities may facilitate the process of undertaking clinical research and translating evidence into practice. Purpose: To (a) identify research priorities for the care of patients and their family as well as for the professional needs of PIC nurses, (b) foster nursing research collaboration, (c) develop a research agenda for PIC nurses. Methods: Over 13 months in 2007—2008, a three-round questionnaire, using the Delphi technique, was sent to all specialist level registered nurses working in Australian and New Zealand PICUs. This method was used to identify and prioritise nursing research topics. Content analysis was used to analyse Round I data and descriptive statistics for Round II and III data. Results: In Round I, 132 research topics were identified, with 77 research priorities (mdn > 6, mean MADmedian 0.68 ± 0.01) identified in subsequent rounds. The top nine priorities (mean > 6 and median > 6) included patient issues related to neurological care (n = 2), pain/sedation/comfort (n = 3), best practice at the end of life (n = 1),and ventilation strategies (n = 1), as well as two priorities related to professional issues about nurses’ stress/burnout and professional development needs.